2009
DOI: 10.1111/j.1364-3703.2008.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

TheMagnaporthe griseaclass VII chitin synthase is required for normal appressorial development and function

Abstract: The plant pathogenic fungus Magnaporthe grisea is able to enter its host via appressorium-mediated penetration. Earlier investigations have shown that these infection structures are rich in the cell wall polysaccharide chitin. Previously, we have described how the transcription of a class VII chitin synthase-encoding gene CHS7 is completely dependent on the putative transcription factor Con7p during the germination of conidia, and how con7(-) mutants are unable to form appressoria under any conditions tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
4
21
1
Order By: Relevance
“…grisea. Microscopy, including 4,6-diamidino-2-phenylindole (DAPI) staining and GFP visualisation, was conducted as described previously (Odenbach et al, 2009). All oligonucleotides used in this study are listed in Table 1 and were obtained from Eurofins-MWG-Operon (Ebersberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…grisea. Microscopy, including 4,6-diamidino-2-phenylindole (DAPI) staining and GFP visualisation, was conducted as described previously (Odenbach et al, 2009). All oligonucleotides used in this study are listed in Table 1 and were obtained from Eurofins-MWG-Operon (Ebersberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Chitin synthases in fungi were previously classified into six categories (Roncero, 2002;Ruiz-Herrera et al, 2002) and a seventh class has recently been identified (Choquer et al, 2004;Mandel et al, 2006;Martín-Udíroz et al, 2008;Kim et al, 2009;Odenbach et al, 2009). A class I chitin synthase gene (CHS1) from F. asiaticum has been shown to play a role during mycelium development (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…This b-1,4-linked polymer of N-acetylglucosamine is synthesized by chitin synthases (CHSs), which are thought to be delivered in secretory vesicles to the growth region (Sietsma et al, 1996;Bartnicki-Garcia, 2006). Studies in numerous fungi have shown that the deletion of CHSs results in a weakening of the cell wall and causes abnormal growth of the fungal hyphae (Fujiwara et al, 1997;Horiuchi et al, 1999;Werner et al, 2007), as well as appressoria (Werner et al, 2007;Odenbach et al, 2009). Consequently, CHSs perform crucial roles in plant infection (e.g., Madrid et al, 2003;Garcera-Teruel et al, 2004;Martin-Udiroz et al, 2004Soulie et al, 2006;Weber et al, 2006;Werner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%